STUDENTS’ ERROR IN WRITING DESCRIPTIVE TEXT IN THE JUNIOR HIGH SCHOOL VIEWED FROM ITS INDICATORS - Yani, Kartika Ketut (Jurnal Pendidikan Bahasa Inggris undiksha, 2021)
Students often make mistakes in writing descriptive texts about people, animals, objects, or procedures. When asked about the source of the error, they did not give a clear answer to the question, let alone an explanation of the source of the error. The purpose of this study was to analyze the types of errors made by students and find out why students made mistakes in writing texts. The method used in this study is a qualitative description. Fifteen seventh-grade junior high school students were the subjects in this study. Data collection was carried out by presenting tests to students to write three descriptive texts about people, animals, and procedures, and focus group interviews on finding out why students made mistakes. The data is based on seven indicators in writing, namely the title, main sentence, significant sentence development, sentence structure, grammar used, word use, and writing, and ten sources of errors that might cause students to make mistakes in writing. This study found that students made mistakes in describing people, animals, and procedures in the title, main sentence, significant sentence development, sentence structure, word choice, grammar, and mechanics. Meanwhile, the highest proportion of students' mistakes in writing is the students' indifference to their writing.